Pengembangan Elektronik Module IPA untuk Meningkatkan Keterampilan Proses Sains Siswa - Siti Alisah; Sajidan Sajidan; Muzzazinah Muzzazinah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This study aims to assess the initial effectiveness of an electronic module focused on Environmental Conservation material in improving students' Science Process Skills (SPS). This e-module was created using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model and has been validated by experts. A medium-scale trial was conducted with a one-group pretest-posttest design involving 25 students from the upper grades. Data related to SPS were collected using pretest and posttest test instruments, then analyzed using the N-gain analysis method to measure the progress experienced in each SPS indicator. The results of the N-gain analysis showed that this e-module was significantly able to improve students' SPS skills. High increases (N-gain ≥ 0.7) were seen in the indicators "Observing" (0.7), "Concluding" (0.8), and "Communicating" (0.7). Meanwhile, the indicators "Using space/time relationships" (0.6), "Measuring" (0.5), "Classifying" (0.6), and "Predicting" (0.5) showed an increase in the medium category (0.3 < N-gain < 0.7) and tended to be high. These results indicate that electronic modules are very efficient in improving students' KPS, making them a viable learning resource and have the potential to be applied more widely.